Modernidad y tradición en la estampa española del siglo XIX - Vega González, Jesusa (Anuario del Departamento de Historia y Teoría del Arte, 1998)
The research on printmaking during the second half of the Eighteenth century allowed the development of new, cheaper and faster way of printing as lithography and xilography. In Spain there was a real effort to introduce the new lithography but the politicial situation prevented the natural development of this technique; it delayed the arrival of the xilography; it hindered the renewal in the teaching of printmaking. However there were moments in which all these techniques were introduced by pioneers. Finally the etching revival took place and with it the new concept of print characteristic of the contemporary age.